Aloe vera leaves potential as a new source of transglutaminase - Cahyo Indarto; Supriyanto Supriyanto; Wahyu Prihanta; Dang Ngoc Hung (AGROINTEK, 2025)
Transglutaminase is an enzyme that catalyzes cross-linking reactions between primary protein chains. This activity can be applied to improve the texture quality of protein-based food products, such as meatballs, and surimi sausage. Elasticity is an important parameter for consumers when choosing these food products. Currently, many chemical compounds of phosphate have been used to increase the elasticity of food products. Therefore, this study aimed to use plant-derived transglutaminase as a gelling agent for food products to replace chemicals. The experiment was carried out by extracting transglutaminase from aloe vera leaves for characterization. The parameters characterized include transglutaminase activity, optimum temperature and pH, molecular weight, as well as inhibiting and activating compounds. The results showed that aloe vera leaves extract had high transglutaminase activity (0.47 U.mg-1), optimum temperature of 40-50°C, pH 5-7, molecular weight of 70-75 kDa, strongly inhibited by Zn2+ ions, and activated in the presence of dithiothreitol (DTT). The high activity shows that aloe vera leaves can be applied as a gelling agent in food products.